The role of religious dormitories and houses in adult education: a case study - Ergül, Sabri. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2015., 2015)
Many students in Turkey have been staying in religious dormitories in order to carry on with their own education. Our education system puts the knowledge needed for the Secondary Schools Selection and Placement Exam (TEOG), Student Selection Exam for University (YGS-LYS), Public Personnel Selection Exam (KPSS) in the storage of the brain but characterizing the education system to cultivate personal quality in education is not important because our education system produces only workers for capitalists. Therefore, moral reasoning capabilities, emotional qualities and empathy are not learnt in state schools. These needs have been fulfilled by Fethullah Gülen’s dormitories and houses in our country.
Keywords: Dormitories -- Turkey.; Islamic religious education -- Turkey.